Architect of air power General Laurence S. Kuter and the birth of the US Air Force - Laslie, Brian D. (University Press of Kentucky, 2017)
"At age 36, Laurence S. Kuter (1905-1979) became the youngest general officer since William T. Sherman. He served as deputy commander of allied tactical air forces in North Africa during World War II and helped devise the American bombing strategy in Europe. Although his combat contributions were less notable than other commanders in the Eighth Air Force, few officers saw as many theaters of operation as he did or were as highly sought-after. After World War II, he led the Military Air Transport Service, Air University, Far East Air Forces, and served as commander-in-chief of the North American Air Defense Command (NORAD). Despite these accomplishments and others, however, Kuter remains widely underappreciated. In Architect of Air Power, Brian D. Laslie offers the first biography of this important but unsung pioneer whose influence can be found in every stage of the development of an independent US Air Force. From his early years at West Point to his days at the Air Corps Tactical School to his leadership role at NORAD, Kuter made his mark with quiet efficiency. He was an early advocate of strategic bombardment rather than pursuit or fighter aviation...fundamentally changing the way air power was used...and later helped implement the Berlin airlift in 1948. In what would become a significant moment in military history, he wrote Field Manual 100-20, which is considered the Air Force's "declaration of independence" from the Army. Drawing on diaries, letters, and scrapbooks, Laslie offers a complete portrait of this influential soldier. Architect of Air Power illuminates Kuter's pivotal contributions and offers new insights into critical military policy and decision-making during the Second World War and the Cold War."...Provided by publisher